Representation of Cultural Values in Digital Content Through a Grounded Theory Approach to Cultural Creators on Tiktok - Arin Mantara Anggawirya; Rosalia Floriani; Abdurrahman Shaleh Reliubun; Martha Betaubun; Desy Eva Laila Rokhmah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze how cultural values are represented and perceived in digital media content, particularly on the TikTok platform. Employing a qualitative grounded theory approach, the research involved nine observations of content creators who share representations of both local and transnational cultures. The data analysis process was conducted in stages using open coding, axial coding, and selective coding, facilitated by NVivo 15 software to support coding, conceptual relationships, and data visualization. The findings reveal that “Educational and Reflective Impact” emerged as the core category representing the main outcome of digital cultural content. This impact arises from the complex interaction of several supporting categories: Cultural Representation, Cultural Values and Tolerance, Presentation Strategies and Appeal, Audience Participation and Response, Consistency and Cultural Commitment, and Digital Communication Ethics. These findings suggest that digital cultural content serves not only as entertainment but also as a medium for social education and cultural reflection, especially when presented authentically, engagingly, and ethically. This study contributes to the field of digital cultural literacy and offers a systematic approach to understanding how culture is communicated, interpreted, and reimagined by global audiences through social media.